Diversification of CORVET tethers facilitates transport complexity in Tetrahymena thermophila - Sparvoli, Daniela; Zoltner, Martin; Cheng, Chao-Yin; Field, Mark C; Turkewitz, Aaron P (Journal of cell science, 2020)
In endolysosomal networks, two hetero-hexameric tethers called HOPS and CORVET are found widely throughout eukaryotes. The unicellular ciliate Tetrahymena thermophila possesses elaborate endolysosomal structures, but curiously both it and related protozoa lack the HOPS tether and several other trafficking proteins, while retaining the related CORVET complex. Here, we show that Tetrahymena encodes multiple paralogs of most CORVET subunits, which assemble into six distinct complexes. Each complex has a unique subunit composition and, significantly, shows unique localization, indicating participation in distinct pathways. One pair of complexes differ by a single subunit (Vps8), but have late endosomal versus recycling endosome locations. While Vps8 subunits are thus prime determinants for targeting and functional specificity, determinants exist on all subunits except Vps11. This unprecedented expansion and diversification of CORVET provides a potent example of tether flexibility, and illustrates how 'backfilling' following secondary losses of trafficking genes can provide a mechanism for evolution of new pathways.This article has an associated First Person interview with the first author of the paper.
Keywords: Cryomilling; Backfilling; Ciliate; lyzozomy; Paralogous expansion; Tetrahymena thermophila; CORVET; Endosomes; lidé; Endosomal trafficking; Lysosomes; endozomy; Humans; Evolutionary cell biology; Vesicular Transport Proteins; Mass spectrometry; vezikulární transportní proteiny